Italy’s five-year plan ex post - CAMPOLONGO, A. (PSL Quarterly Review, 2014)
The five-year period covered by Italy’s first national economic Plan came to an end in December last year, so now it is possible to make a limited statistical assessment ex post of its results. The author confines comments to a few of the quantitative forecasts made, without analysing the cause of the divergence between forecasts and actual performance. Some of the Plan’s forecasts were confirmed or even exceeded by the actual performance: growth rate of GNP, expansion of the industrial and tertiary sectors, private saving, foreign trade and overall surplus of the balance of payments. Others, on the contrary, failed more or less seriously to materialise: employment, price stability, the gap in the Mezzogiorno, propensity to consume, public saving, financing of investments and exports of capital. JEL: E60, E24, O47, O52